The Nexus between city livability and transportation in Lagos Metropolis, Nigeria - AKANMU Ayobami Ademola; GBADAMOSI Kolawole Taofeek; OMOLE Felix Kayode (Logistics, Supply Chain, Sustainability and Global Challenges, 2022)
The livability of cities has been a matter of global concern in recent times. Importantly, the ease of mobility and accessibility in cities remained paramount factors in enhancing residents’ locational decisions and suitability. It is on this basis that this study examined the nexus between city livability and transportation in the Lagos Metropolis, Nigeria. Anchored on the concept of livability, the study descriptively and inferentially analyzed the results of 1264 questionnaires administered to residents based on key livability themes. The study revealed low satisfaction with the livability key performance indicators. Similarly, the study revealed that most of the assessed transportation infrastructure facilities are in poor condition and thus hinder the ease of commuting and livability in the city. The result of the regression analysis revealed that transportation infrastructure statistically influenced the livability of the Lagos metropolis. The study recommends the need for expedited proactive measures, particularly structural improvement in transportation infrastructure, towards improving the livability of the Lagos Metropolis.